2008
DOI: 10.1248/cpb.56.485
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Analysis of Swertia Herbs by High Performance Liquid Chromatography-Diode Array Detector-Mass Spectrometry (HPLC-DAD-MS)

Abstract: We evaluated the composition of Swertia herbs using high performance liquid chromatography-diode array detector-mass spectrometry (HPLC-DAD-MS). Eleven peaks of 6 species were unequivocally identified by comparing their retention times, UV spectra, on-line electrospray ionization mass (ESI-MS) spectra, and collision-induced dissociation mass spectrometry/mass spectrometry (CID-MS/MS) data with those of authentic compounds. We adopted wavelengths of 254 nm, 340 nm and 230 nm to simultaneously determine these 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Materials used in this study are summarized in Table 1; they were the same materials used in a previous study [4]. Cultivated Swertia japonica specimens were collected in Nagano Prefecture, Japan.…”
Section: Plant and Crude Drug Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Materials used in this study are summarized in Table 1; they were the same materials used in a previous study [4]. Cultivated Swertia japonica specimens were collected in Nagano Prefecture, Japan.…”
Section: Plant and Crude Drug Materialsmentioning
confidence: 99%
“…These biological effects are attributable to the major and characteristic groups of the chemical constituents of Swertia plants (xanthones, iridoids and flavonoids). Recently, chemical constituent profiling of the crude drugs derived from four Yunnanese Swertia plants and Japanese S. japonica as well as S. pseudochinensis Hara from Hebei Province was conducted using LC/MS/MS [4]. The results showed the following similarities and differences in chemical profile of the major constituents of the 6 species: (1) S. japonica and S. pseudochinensis showed high swertiamarin content and universal occurrence of irridoids and flavonoids, (2) S. decora Franch and S. delevayi Franch showed high swertiamarin but very low xanthones and flavonoids content, (3) S. binchuanensis T. N. Ho & S. W. Liu and S. punicea Hensl had relatively high flavonoids content.…”
Section: Introductionmentioning
confidence: 99%
“…18,19,20 In the Cecropia genus, quantitative analysis of chlorogenic acid has been reported only for C. obtusifolia. The contents of this compound in the leaves of this species are in the range of 3.0-13.2 mg g -1 of dry weight.…”
Section: Quantification and Validation Proceduresmentioning
confidence: 99%
“…Gentiana siphonantha Maxim., a perennial herb in the Gentianaceae family, has been a traditional Chinese medicine for more than 2000 years for the treatment of rheumatoid arthritis, jaundice hepatitis, constipation, pain, and hypertension [25,26,27]. Previous studies on G. siphonantha have shown that this medical herb is rich in iridoids, especially gentiopicroside [28,29], well-known phytochemicals in a number of folk medicinal plants with anti-inflammatory, antibacterial, free radical-scavenging, and hepatoprotective activities [30,31,32,33]. The above plants have anti-inflammatory, analgesic or swelling-decreasing activities.…”
Section: Introductionmentioning
confidence: 99%